Research Progress on the Structure and Function of G3BP - Kang, Weifang; Wang, Yue; Yang, Wenping; Zhang, Jing; Zheng, Haixue; Li, Dan (Frontiers in Immunology, 2021)
Ras-GTPase-activating protein (SH3 domain)-binding protein (G3BP) is an RNA binding protein. G3BP is a key component of stress granules (SGs) and can interact with many host proteins to regulate the expression of SGs. As an antiviral factor, G3BP can interact with viral proteins to regulate the assembly of SGs and thus exert antiviral effects. However, many viruses can also use G3BP as a proximal factor and recruit translation initiation factors to promote viral proliferation. G3BP regulates mRNA translation and attenuation to regulate gene expression; therefore, it is closely related to diseases, such as cancer, embryonic death, arteriosclerosis, and neurodevelopmental disorders. This review discusses the important discoveries and developments related G3BP in the biological field over the past 20 years, which include the formation of SGs, interaction with viruses, stability of RNA, and disease progression.